PRODEKTIF: Pengolahan Sampah Organik Konsep Pentahelix Menuju Ekonomi Desa Berkelanjutan - Irawan, Hendri; Pradanna, Satrio Alpen; Anggraeni, Leni; Wijayanti, Tutik; Anggraeni, Alvi (Universitas Tabanan, 2024)
The Central Statistics Agency (BPS) recorded Indonesia's poverty rate at 26.36 million people in 2022, an increase of 0.04 million compared to the previous year. Poverty is an issue that must be addressed to achieve sustainable development (SDGs), particularly SDG 1, which aims to eradicate poverty. Organic waste is a potential resource in rural areas that can be economically utilized, creating business opportunities and jobs at the village level. This study explores PRODEKTIF (Productive Village Program), focusing on optimizing organic waste management through the Pentahelix concept to accelerate sustainable rural economic development. The research employs a qualitative approach using case study methods involving active participation from village communities, local governments, businesses, educational institutions, and community organizations in program development. The results show that increasing community productivity through the PRODEKTIF program promotes sustainable rural economic development by implementing the Pentahelix concept, which engages five key stakeholders: government, businesses, educational institutions, community organizations, and the community itself. The findings of this study are expected to serve as a reference for governments, educational institutions, and communities in developing similar programs focused on organic waste management and rural economic empowerment.